Severe secondary hyperparathyroidism in patients on haemodialysis is associated with a high initial serum parathyroid hormone and beta-CrossLaps level: Results from an incident cohort. - Guillaume Jean; Marie Hélène Lafage-Proust; Jean Claude Souberbielle; Sylvain Lechevallier; Patrik Deleaval; Christie Lorriaux; Jean Marc Hurot; Brice Mayor; Manolie Mehdi; Charles Chazot (PLoS ONE)
Background Secondary hyperparathyroidism (SHPT) is a frequent complication of renal disease and most commonly occurs in patients on haemodialysis (HD) with metabolic, vascular, endocrine, and bone complications. The aim of this study was to analyze the evolution of mineral metabolism parameters during the first 36 months of HD treatment and identify the initial factors associated with severe SHPT. Methods Serum parathyroid hormone (PTH), calcium and phosphate levels were measured monthly; bone-specific alkaline phosphatase (b-ALP) and beta-CrossLaps (CTX) were measured biannually. Severe SHPT was defined as the need for cinacalcet treatment. Patients with less than 24 months of follow-up were excluded. Results One hundred thirty-three incident HD patients were included. Baseline mean PTH was 275 ± 210 pg/mL. After an initial drop at the third month (172 ± 133 pg/mL), the serum PTH level progressively increased to the maximum at 36 months (367 ± 254 pg/mL). This initial drop was associated with the initial correction of both hypocalcaemia and hyperphosphataemia. Serum CTX and b-ALP revealed no significant changes over time. Severe SHPT was observed in 18% of patients and was associated with higher mean calcaemia and phosphataemia. In logistic regression, the initial factors associated with the risk of severe SHPT were: female sex, higher baseline PTH and CTX values. A receiver operation characteristic curve analysis identified a cut-off value of >374 pg/mL for baseline PTH and >1.2 μg/L for CTX for increased risk of developing severe SHPT. The relative risk of developing severe SHPT was 3.7 (1.8-7.5, p = 0.002) for high baseline CTX, 4.9 (2.4-9.7, p = 0.001) for high baseline PTH, and 7.7 (3.6-16, p< 0.0001) when both criteria were present. Conclusion After an initial drop, a progressive increase in the serum PTH level during the first 3 years of HD treatment was observed despite aggressive therapy. High baseline levels of PTH and CTX increased the risk of developing severe SHPT.